2005
DOI: 10.1016/j.nuclphysa.2005.02.087
|View full text |Cite
|
Sign up to set email alerts
|

A search for deeply bound kaonic nuclear states

Abstract: We have measured nucleon energy spectra by means of time-of-flight (TOF) from 4 He(K − stopped , N) reactions (KEK PS E471 experiment). In the proton spectrum, a clear mono-energetic peak was observed under semi-inclusive condition, which was assigned to the formation of a strange tribaryon S 0 (3115) with isospin T = 1. The mass and width of the state were deduced to be 3117.7 +3.8 −2.0 (syst) ± 0.9(stat) MeV/c 2 and < 21.6 MeV/c 2 , respectively, and its main decay mode was ΣNN. In the neutron spectrum, a mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Motivated by the conjecture that a very strong K − nucleon potential could form a deeply bound K − ppn state [47] a systematic experimental search has been launched at the KEK facility. The first results by Suzuki et al [48] showed a structure in the missing-mass spectra in the 4 He(K − stopped , p) reaction which -due to kinematic reasons -cannot be due to hypernucleus formation (K − + 4 He) atomic → π − + 4 Λ He, 4 Λ He → p + 3 Λ H. This structure has been identified with two deeply boundKNNN states (K − + 4 He) atomic → S 0 (3115) + p (47) and (K − + 4 He) atomic → S + (3140) + n.…”
Section: Deeply Bound Kaonic States In Nucleimentioning
confidence: 94%
“…Motivated by the conjecture that a very strong K − nucleon potential could form a deeply bound K − ppn state [47] a systematic experimental search has been launched at the KEK facility. The first results by Suzuki et al [48] showed a structure in the missing-mass spectra in the 4 He(K − stopped , p) reaction which -due to kinematic reasons -cannot be due to hypernucleus formation (K − + 4 He) atomic → π − + 4 Λ He, 4 Λ He → p + 3 Λ H. This structure has been identified with two deeply boundKNNN states (K − + 4 He) atomic → S 0 (3115) + p (47) and (K − + 4 He) atomic → S + (3140) + n.…”
Section: Deeply Bound Kaonic States In Nucleimentioning
confidence: 94%
“…Two claims of the observation of kaonic bound states were put forward by the E471 collaboration: the S 0 (3115) [91] and the S + (3140) [97,98]. Figure 7 shows on the left panel the missing momentum of the spectator proton in the reaction K −4 He → p(π) + X, where the peak at around 500 MeV/c was interpreted as the evidence of the S 0 (3115), a K − npp bound state with a width of < 20 MeV.…”
Section: Experimental Determination Ofkn Nmentioning
confidence: 99%
“…The extracted mass and width of the state are 3117.0 +1.5 −4.4 MeV and < 21 MeV, respectively, and its main decay mode is found to be ΣNN. The recent detailed analysis of the neutron spectrum in 4 He(K − stopped , n) [2] has made manifest a second monoenergetic peak assigned to the formation of another strange tribaryon S + (3140) with a significance of 3.7σ. The mass and width of this state are deduced to be 3140.5 +3.0 −0.8 (syst) ± 2.3(stat) MeV and < 21.6 MeV, respectively, its main decay mode being Σ ± NN.…”
Section: Introductionmentioning
confidence: 99%